Recurrent atelectasis in a preterm neonate - Kamalammal, Rugmini; M., Venkatamurthy; M., Niranjan (International Journal of Contemporary Pediatrics, 2016)
Excessive or thick pulmonary secretions obstructing the small airways are a common problem in neonatal population. Pulmonary collapse may occur secondary to mucus plug. Recombinant - DNase is thought to improve atelectasis by decreasing viscosity and assisting mucociliary clearance in cases of pulmonary collapse. Inhaled hypertonic saline is tried as an alternative. Here we report a case of respiratory distress syndrome with collapse of entire left lower lobe which is very rare and it responded significantly to hypertonic saline nebulisation along with chest physiotherapy and regular suctioning. Atelectasis is common in post extubated neonates but in our case it developed in pre intubation period. Here we highlight the fact that nebulized hypertonic saline can be an effective alternative to recombinant DNase in resource limited settings like in India.